1989
DOI: 10.1029/ja094ia09p11739
|View full text |Cite
|
Sign up to set email alerts
|

Basic properties of solar wind MHD turbulence near 0.3 AU analyzed by means of Elsässer variables

Abstract: and Alfv6n velocity fluctuations, respectively. For small amplitude Alfv6n waves the fluctuation variable •Z + simply relates to outward propagation and •Z-to an inward sense of propagation, if the ambient magnetic field Bo is directed inward. The frequency range analysed in this paper is 6 x 10 -6 Hz to 6 x 10 -3 Hz. It is found that (1) the autocorrelation length for $Z-is much larger than for/SZ + in both the high-speed and low-speed wind. (2) The power spectra of •Z-, especially in high-wind speed, are ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 62 publications
16
125
1
Order By: Relevance
“…15, cases (c) and (d) in Table 2. We can generally notice only small differences between z + and z − , and therefore the outgoing and ingoing fluctuations seem to be similar, which is roughly consistent with equipartition suggested by Tu et al (1989). On the other hand, behind the bow shock for small plasma β ∼ 1 (when the thermal pressure and the magnetic pressure are similar in the magnetized plasma), but with a moderate Alfvénic Mach number M A ≈ 9, Fig.…”
Section: Results For the Magnetosheathsupporting
confidence: 66%
“…15, cases (c) and (d) in Table 2. We can generally notice only small differences between z + and z − , and therefore the outgoing and ingoing fluctuations seem to be similar, which is roughly consistent with equipartition suggested by Tu et al (1989). On the other hand, behind the bow shock for small plasma β ∼ 1 (when the thermal pressure and the magnetic pressure are similar in the magnetized plasma), but with a moderate Alfvénic Mach number M A ≈ 9, Fig.…”
Section: Results For the Magnetosheathsupporting
confidence: 66%
“…High Reynolds numbers in combination with massive energy injection, as seen in, e.g., the solar wind, are strong indicators of a highly turbulent state. In situ measurements of the energy spectrum (Tu et al 1989) agree with this fact. To simulate conditions within the turbulent heliospheric plasma, the research group at the University of Würzburg has developed a simulation code, Gismo.…”
Section: Numerical Modelsupporting
confidence: 74%
“…Here we employ the Karman-Taylor approach for modeling the evolution of λ C and Z (Matthaeus et al 1998), obtaining the scalings λ C (r) ∼ √ (r) and Z 2 (r) ∼ 1/r (Matthaeus et al 1998). Then, the corresponding MHD timescale, in case of zero cross-helicity, is t NL (r) = λ C (r)/Z(r) ∼ r. However, this simplification is well satisfied beyond a few astronomical units (AU), but it is not a reasonable simplification at distances less than 1 AU from the Sun (Tu et al 1989). Matthaeus et al (2004) have shown that for nonzero cross-helicity σ c , along with the equations for the evolution of λ C and Z, a third simplified equation for σ c can be written, which causes a reduction in the effective decay of the above quantities by a factor f. In turn, the nonlinear time becomes t NL (r) = f λ C (r)/Z(r), where f is a function of σ c and it is defined as (1…”
Section: Comparison Between Solar Wind and Simulation Datamentioning
confidence: 96%
“…Therefore, the fact that plasma data (81 s) are not available at the cadence of the magnetic field data (6 s) does not present a problem for the computation of the global cross-helicity. This is however the reason we did not consider analysis in terms of Elsasser fluctuation variables (Tu et al 1989), staying instead with magnetic field fluctuations.…”
Section: Comparison Between Solar Wind and Simulation Datamentioning
confidence: 99%